1999
DOI: 10.1021/jp984489i
|View full text |Cite
|
Sign up to set email alerts
|

HOBr in Sulfuric Acid Solutions:  Solubility and Reaction with HCl as a Function of Temperature and Concentration

Abstract: A detailed study of the interaction of HOBr and HCl in cold sulfuric acid solutions has been performed using a coated-wall flow tube coupled to an electron-impact mass spectrometer. The liquid-phase bimolecular rate constants, measured over a temperature range from 213 to 238 K and in solutions from 59.7 to 70.1 wt % composition, show a strong positive dependence on both acid composition and temperature. The solubility of HOBr has also been measured in these solutions by analyzing its time-dependent uptake. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
52
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(60 citation statements)
references
References 21 publications
8
52
0
Order By: Relevance
“…For simplicity in deriving the rate coefficient for in bulk solution, it is assumed that the contribution of the surface reaction is negligible. The measurements of by Waschewsky and Abbatt [1999] are consistent with this assumption. The lines are fits according to The second relation comes from and shows the relation between the parameter a and H HCl * , D l , H HOBr , and k II .…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…For simplicity in deriving the rate coefficient for in bulk solution, it is assumed that the contribution of the surface reaction is negligible. The measurements of by Waschewsky and Abbatt [1999] are consistent with this assumption. The lines are fits according to The second relation comes from and shows the relation between the parameter a and H HCl * , D l , H HOBr , and k II .…”
Section: Resultssupporting
confidence: 77%
“…This is not surprising as it was found that H HOCl [ Donaldson et al , 1997] also does not vary strongly with sulfuric acid content over this range (from 1.7 × 10 3 to 1 × 10 3 M atm −1 ). The independence of H HOBr with acid content was also reported by Waschewsky and Abbatt [1999]. However, extrapolation of their data to 250 K (they report measurements from 208 to 238 K) results in a value for H HOBr of 3 × 10 4 M atm −1 , much lower than the average of the values shown in Figure 6 of 1.4 × 10 5 M atm −1 .…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…The Henry's law constants were measured at bulk liquid conditions, which is very different from the quasi‐liquid surface layer of snow and aerosols where the reactions take place [e.g., Koop et al , 2000]. Additional uncertainties could come from the mass accommodation coefficients and their temperature dependence [e.g., Waschewsky and Abbatt , 1999]. Similar kinetic uncertainties also exist for HOBr uptake.…”
Section: Nmhcsmentioning
confidence: 99%